PERANAN DESA ADAT DALAM PENYELESAIAN SENGKETA TANAH LABA PURA SAMUAN TIGA, DESA ADAT BEDULU, KECAMATAN BLAHBATUH, KABUPATEN GIANYAR - Nyoman Yoana Adisubiksa; I Wayan Wahyu Wira Udytama (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Desa Adat is one of the traditional social organizations in Bali, led by the Bendesa adat. The Bali Provincial Government provides protection for the existence of Traditional Villages through the Bali Provincial Regulation Number 4 of 2019 concerning Traditional Villages in Bali. The formulation of the problem in this research is what is the role of the traditional village in resolving land disputes over Samuan Tiga Temple profits and what factors influence the role of traditional villages in resolving land disputes over Samuan Tiga Temple profits. The data collection method used by researchers consisted of interviews and documentation studies. The results of the study show that the role of the Traditional Village in handling land disputes is not optimal. This is because there are no village regulations or awig-awig that regulate this problem. Lack of socialization and also approach with the community is also one of the factors that often causes these problems.